The crystal structure of bicyclol, C19H18O9 - Wang Fengfeng; Hu Xiaowen; Zhang Caiyu; Luan Lin; Liu Yang (Zeitschrift für Kristallographie - New Crystal Structures)
C19H18O9, monoclinic, P21/c (no. 14), a = 8.82839(18) Å, b = 15.3431(3) Å, c = 13.4413(3) Å, β = 97.3429(18)°, V = 1805.76(6) Å3, Z = 4, Rgt(F) = 0.0399, wRref(F2) = 0.1167, T = 297 K.